2017
DOI: 10.1021/acs.organomet.7b00256
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic C–H σ-Bond Activation by Ni0, Pd0, and Pt0 Alkene Complexes: Concerted Oxidative Addition to Metal vs Ligand-to-Ligand H Transfer Mechanism

Abstract: C−H σ-bond activation of arene (represented here by benzene) by the Ni 0 propene complex Ni 0 (IMes)-(C 3 H 6 ) (IMes = 1,3-dimesitylimidazol-2-ylidene), which is an important elementary step in Ni-catalyzed hydroarylation of unactivated alkene with arene, was investigated by DFT calculations. In the Ni 0 complex, the C−H activation occurs through a ligand-to-ligand H transfer mechanism to yield Ni II (IMes)(C 3 H 7 )(Ph) (C 3 H 7 = propyl; Ph = phenyl). In Pd 0 and Pt 0 analogues, the activation occurs throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 92 publications
6
77
0
Order By: Relevance
“…The activation of Ar–H bond by Ni, Pd, and Pt NHC-complexes was calculated at the M06/6-311G(d)&SDD//M06/6-31G(d)&LANL2DZ level of theory with bulk solvent effects modeled with C-PCM method. 631 The authors showed that while Pd and Pt easily form the [(NHC)Ar-M-H(alkyl)] hydride complex, Ar–H activation on the Ni-NHC complexes proceeds through the direct aryl-to-alkyl transfer, with propene being the proton acceptor and the coupling partner, which is a consequence of the Ni–H bond weakness and the lower aryl-to-alkyl distance in the Ni species. It should be noted that in C–H activation by 3d transition metals, the so-called two-state reactivity phenomenon is common which makes the computational modeling of these rather challenging ( vide infra ).…”
Section: Mechanistic Complexity In Catalysis By 3d Transition Metalsmentioning
confidence: 99%
“…The activation of Ar–H bond by Ni, Pd, and Pt NHC-complexes was calculated at the M06/6-311G(d)&SDD//M06/6-31G(d)&LANL2DZ level of theory with bulk solvent effects modeled with C-PCM method. 631 The authors showed that while Pd and Pt easily form the [(NHC)Ar-M-H(alkyl)] hydride complex, Ar–H activation on the Ni-NHC complexes proceeds through the direct aryl-to-alkyl transfer, with propene being the proton acceptor and the coupling partner, which is a consequence of the Ni–H bond weakness and the lower aryl-to-alkyl distance in the Ni species. It should be noted that in C–H activation by 3d transition metals, the so-called two-state reactivity phenomenon is common which makes the computational modeling of these rather challenging ( vide infra ).…”
Section: Mechanistic Complexity In Catalysis By 3d Transition Metalsmentioning
confidence: 99%
“…Finally, the lack of an oxidizing Ni/H interaction at the transition state is not solely due to the expected difficulty in oxidizing a Ni(II) cationic centre, as a similar absence of redox character has been suggested for s-bond exchanges involving Ni(0) centres, 79,80 but this does not extend to heavier metals of Group 10. 81 The two catalytic cycles of Scheme 3 are quite similar and are based on reactions of analogous hydride (cycle A) or silyl (cycle B) complexes. In A, the silyl group migrates to an alkyl ligand, while in B, hydride migrates to a silyl-substituted alkyl ligand.…”
Section: Discussion Of the Mechanismmentioning
confidence: 99%
“…The LLHT mechanism is now commonly proposed in many catalytic reactions involving the addition of a C-H bond to C-C multiple bond. 67,[136][137][138] In 2017, Sakaki performed an in-depth DFT study of the C-H activation of benzene by Ni(0)-, Pd(0)-and Pt(0)-propene complexes. 136 In the case of the Ni(0) complex, C-H bond activation occurs via a LLHT mechanism without generating a Ni(II) hydride phenyl intermediate because of the compact size of the nickel metal which decreases the distance between the benzene and alkene in the transition state and the intermediate.…”
Section: Reviewmentioning
confidence: 99%